Intraoperative transcranial embolization following decompressive craniectomy for a dural arteriovenous fistula presenting with acutely raised intracranial pressure - Giragani, Suresh; Kasireddy, Ashok; Balasubramaniam, Anandh; Agrawal, Vikas; Muthyala, Swathi (Asian Journal of Neurosurgery, 2020)
We report the clinical details, imaging findings, and management of a 58-year-old female who presented with rapidly deteriorating neurological function and acute raise in intracranial pressure secondary to posterior fossa dural arteriovenous fistula (DAVF). In this report, we present the emergency management of the DAVF with single-stage combined surgical decompressive craniotomy and direct transcranial embolization.
Keywords: Dural arteriovenous fistula; surgical approach; transcranial embolization